“Scarabò” and the Educating City. Pedagogical Reflections on some Results of a Field Research - Fabrizio d’Aniello (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
“Scarabò. A city to educate” is an education festival, which takes place in the old city of Macerata (IT) every year. A complex field research activity is focused on the 2018 and 2019 editions. This research was motivated by the participation in the international Trans-Urban EU-China project, devoted to the study of the relationship between urban sustainability and social integration/inclusion. Only some results of the interviews given by 116 adults participating in the 2018 festival are reported on this occasion, pedagogically focusing on the topic of the educating city.